What Makes Them Snap? Gratifications of Using Snapchat by Generation Z - Aakash Kamble; Supriya Desai; Smita Mehendale (Asian Academy of Management Journal, 2021)
This paper aims to understand the motivations and behavioural patterns of Snapchat use by Generation Z (Gen-Z) and their social relationships with friends and romantic companions. Focus group discussion and in-depth interview methodology were employed to conduct the research with 49 respondents participating in focused group discussions. The respondents reported Snapchat being adopted for connecting with friends as it provided them with secure and authentic experience over other social media platforms. The gratifications gained from the use of Snapchat by Gen Z users were identified emerging from the features and experience of using the technology platform. The results were supported for uses and gratifications as the respondents justified the ephemerality of Snapchat being useful, the gratifications gained from snapping with friends and social groups. Snapchat was seen as a useful medium for security, privacy and ephemerality it provided along with a medium for authentic communications with friends and romantic companions.